THE ROLE OF HUMAN CAPITAL IN AGRIBUSINESS MUHAMMADIYAH CENTER AS A STRATEGY TO INCREASE INNOVATION IN FACING THE WORLD OF WORK - Basuki, Agus Tri; Yuliadi, Imamudin; Leli, Diana; Supardin, Lalu (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
Muhammadiyah Agribusiness Center (MAC) is an institution established by the Muhammadiyah Branch Leadership to empower Muhammadiyah residents in Gamping District in the agribusiness sector. As part of the Muhammadiyah movement, MAC has an important role in strengthening the rural economy and improving the welfare of agricultural communities. This service aims to improve the understanding and skills of Muhammadiyah Agribusiness Center (M.A.C.) residents in managing independent businesses and product innovation, so that they can manage their businesses effectively. Community service is carried out using the Participatory Action Research (PAR) method, involving community members as research partners in identifying needs, developing strategies, training, and implementing solutions. The results of this Community Service are that participants who take part in this training experience increased abilities in managing independent businesses, this is evidenced by active discussions between participants and speakers. In addition, by taking part in this training, basic understanding of innovation in managing business ventures has also increased. In general, through this program, it is hoped that M.A.C. members will be more confident and independent in improving family welfare through independent businesses and supporting development.